Analisis Kelayakan Rencana Pengembangan IKM Kerupuk Jengkol di Sentra IKM Kerupuk, Kecamatan Jayanti, Kabupaten Tangerang - Haifan Mohamad Haifan (Institut Teknologi Indonesia, 2021)
Jengkol fruit (Archidendron pauciflorum B) is one of the fruits that is attractive to the public, besides being able to attract appetites, jengkol fruit also has many health benefits. One of the uses of jengkol fruit is used as raw material for making crackers. The demand for jengkol crackers continues to increase every year, so the prospect for business opportunities is good. Seeing this opportunity, it is necessary to increase the production capacity of jengkol cracker industry / Small and Medium Scale Industry (SMI) to meet community demand. This study aims to analyze the feasibility of the industrial development plan / IKM cracker jengkol in the IKM kerupuk center area in Jayanti District, Tangerang Regency. The method used in this research is descriptive-quantitative. Analysis of the feasibility of the jengkol cracker IKM development plan includes aspects of raw materials, aspects of technology and aspects of finance. Based on the research results, it was found that the availability of jengkol raw materials to support the industry / IKM was very adequate, which came from the Banten Province, process technology and machinery and equipment were already available and controlled. Analysis of the financial aspects assuming the economic age of the business for five years using an interest rate of 9.75 percent gives a positive Net Present Value (NPV) of IDR 857,492,977; Internal Rate of Return (IRR) of 28.64 percent, Benefit / Cost (B / C Ratio) of 1.10; Payback Period (PP) for 2 years 6 months and Break Event Points (BEP) of 154,104 packages per year. Meanwhile, the sensitivity analysis carried out an increase in production costs by five percent and a decrease in the amount of production by five percent obtained a calculation of the business that was still feasible to run.